East-west dialogue on Jalaluddin Rumi and Ralph Waldo Emerson in relation to mysticism - Livani, Hosseinali (2013)
This research explores and compares the mystical and philosophical ideas of microcosm and macrocosm in selected works of Molana Rumi and Emerson. Excavating these ideas in the selected works helps us to understand that these two writers have similarities of thought in the depiction of the concepts. Therefore, the concepts have been explored from two main sections. One is from the Greek‟s philosophical point of view and the other from the Muslim‟s. In this regard, we investigated the history, meaning and the purpose of applying these concepts in this research. Greek and Muslim philosophers believe that microcosm is the human being and macrocosm is the universe or the cosmos. They called human being, the microcosm because they believed that he is a tiny replica of the universe or the macrocosm. Their purpose to imply these concepts in their philosophical and literary works was to establish the relationship of Man and the universe and to consider the position of Man in the cosmos. Both of these philosophers believe that there are correspondences within material and spiritual dimensions of Man and the universe by which they mirror themselves. Molana Jalauddin Rumi (1207-1273), Persian poet and Muslim Sufi, has dealt profoundly with the concepts of microcosm and macrocosm, in his Masnavi-e-Manavi. Molana Rumi‟s depiction of the microcosmic Man revolves around the Islamic concept of the “Perfect Man.” On the other hand,the American transcendentalist Ralph Waldo Emerson (1803-1882), shares common mystical and philosophical roots in his collected works of the first and second series, despite his geographical distance and abiding in a quite different historical epoch. Although we cannot call Emerson, a mystic, this comparative study excavated the meaning and origin of these concepts and investigates them in the works of both writers.